Quantified economic and environmental values through Functional Productization: a simulation approach - Reed, Sean; Karlberg, Magnus; Kyosti, Petter; Sas, Daria (Elsevier, 2018)
Industrial companies rely on hardware and services from external providers to deliver functions that are critical to their operations, increasingly demanding solutions that not only meet technical and availability requirements but are sustainable too. Traditionally, industrial companies choose and purchase hardware and maintenance support to fulfil their functional requirements. An alternative arrangement, known as Functional Product (FP), involves external providers supplying customers with the functionality they require through contracts that specify guaranteed functional availability whilst giving providers freedom to choose and retain ownership of the supplied hardware and services. This paper describes an innovative simulation modelling and optimization approach to quantitatively compare economic and environmental values resulting from transition from traditional to FP arrangements. The approach is demonstrated through the analysis of a scenario involving a hydraulic drive system provider and set of customers in Sweden, with the results exhibiting simultaneous improvement in economic and environmental values at each stage of the transition.